The prevalence of orthorexia nervosa among gym participants from Croatia: an observational study - Edita Ružman; Orjena Žaja; Jadranka Karuza; Ines Banjari (Acta Clinica Croatica)
Orthorexia nervosa (ON) is pathological obsession and preoccupation with ‘healthy’ and ‘clean’ eating, which is more pronounced in specific population groups such as fitness enthusiasts. The aim of this observational study was to determine the prevalence and characteristics of ON symptoms among gym attendees in Croatia based on ORTHO-15 questionnaire. A number of individual characteristics were considered too, from eating habits, anthropometry, personality traits, psychophysical state, to the presence of irritable bowel syndrome symptoms. Out of 126 participants who completed the questionnaire, 99 were analyzed (female 68.7% and male 31.3%, median age 24 years). Based on the traditional criterion (ORTHO-15 score <40), the prevalence of ON was 77.8% and 33.3% according to the modified criterion (ORTHO-15 <35). Women were two times more likely to have high ON tendency in comparison to men (39.7% vs. 19.4%, p=0.037). Participants with high ON tendency avoided a wide variety of foods, especially sugar, processed food and gluten, and did not skip meals. Th ere were no significant differences in orthorexic tendencies according to nutritional status, personality traits, psychophysical state, or irritable bowel symptoms. For gym attendees in Croatia, being a woman and dietary restrictions were identified as independent risk factors for ON.